Distinctive biochemical properties of the μ-opioid receptor-corticotropin- releasing factor CRF1 receptor heterotetramer - William N. Sanchez; Estefanía Moreno; Marc Ciruela-Jardí; Nil Casajuana-Martín; Anne Yauch; Ning-Sheng Cai; Cesar Quiroz; Ya Gin Chang; Vicent Casadó; Leonardo Pardo; Leigh D. Plant; Sergi Ferré (Pharmacological Research)
Heteromerization of Gs with Gi protein-coupled receptors has been suggested to be necessary to sustain the canonical Gi-Gs antagonistic interaction at adenylyl cyclase (AC). These heteromers have a tetrameric quaternary structure, composed by two homodimers each one coupled to its corresponding G protein. We describe the heterotetramer formed by the Gi-coupled μ-opioid receptor (MOR) and the Gs-coupled corticotropin releasing factor CRF1 receptor (CRF1R), which also sustains a canonical interaction at AC and reciprocal allosteric interactions between MOR and CRF1R ligands. In addition, we found that CRF1R can also couple to Gq proteins in the MOR-CRF1R heteromer, providing the frame for also canonical Gi-Gq antagonistic interactions that include other effectors, such as phospholipase C and its Ca2 + -dependent signaling, and which control glutamate release in the central amygdala (CeA). The specific pharmacodynamic properties of the MOR-CRF1R heteromer, including its sensitivity to S-methadone, as well as its localization in the CeA suggest it might represent a significant pharmacological target for the analgesic, antistressor and antidepressant effects of opioids and the hyperalgesia of opioid withdrawal.